Multiplexed SERS Detection of Serum Cardiac Markers Using Plasmonic Metasurfaces - Peng Zheng; Lintong Wu; Piyush Raj; Jeong Hee Kim; Santosh Kumar Paidi; Steve Semancik; Ishan Barman (Advanced Science)
Abstract Surface‐enhanced Raman spectroscopy (SERS) possesses exquisite molecular‐specific properties with single‐molecule sensitivity. Yet, translation of SERS into a quantitative analysis technique remains elusive owing to considerable fluctuation of the SERS intensity, which can be ascribed to the SERS uncertainty principle, a tradeoff between “reproducibility” and “enhancement”. To provide a potential solution, herein, an integrated multiplexed SERS biosensing strategy is proposed, which features two distinct advantages. First, a subwavelength‐structured plasmonic metasurface consisting of alternately stacked metal–dielectric pyramidal meta‐atoms is fabricated and could provide simultaneously enhanced electric and magnetic fields to enable spatially extended and weakly wavelength‐dependent SERS. Second, nanomechanical perturbations are harnessed to transduce signals in the form of SERS frequency shifts, which are not directly affected by the SERS uncertainty principle. By also employing 3D printing methods, a proof‐of‐concept study of multiplexed detection of a panel of serum cardiac biomarkers for acute myocardial infarction is provided. Success in the development of both the electric and magnetic fields‐active plasmonic metasurfaces could transform future designs of SERS substrates with newly endowed functionalities, and frequency shift‐based SERS multiplexing could open new opportunities to develop innovative quantitative optical techniques for applications in chemistry, biology, and medicine.